Performance analysis of capacitor voltage balancing in modular multilevel converter by sorting algorithm - Amel Ahmad Ridha; Ali Salam Al-Khayyat; Haider Fadel (Institute of Advanced Engineering and Science, 2022)
Due to the modularity of modular multilevel converter (MMC), therefore it has been considered as a substitute for the diode-clamp multilevel inverter in applications of high-voltage high-power. Where it can obtain any level of voltage without imposing complexity on the control system. This study analyses in detail the operation principle and balances the capacitor voltage of sub-module (SM) in modular multilevel converter by sorting algorithm. The output voltage control and capacitor voltage balancing technique are confirmed by MATLAB/Simulink and the obtained result has been discussed, where the capacitor voltage of the sub-module has controlled within the acceptable deviation limit, which is 5-10%. In addition, the circulating current has been controlled and reduced.